The macroeconomic determinants of renewable energy consumption in Madagascar: Evidence from an Autoregressive Distributed Lag modeling approach - Ramaharo, Franck; Razanajatovo, Yves, Heritiana, Mihaja (My University, 2024)
We investigate the macroeconomic determinants of renewable energy consumption in Madagascar, using annual data from 1990 to 2021 and the ARDL bounds testing approach. Our results reveal that, in the long run, domestic investment, financial development, trade openness and foreign direct investment have a significant and positive impact on renewable energy consumption. Conversely, increased economic growth, industrial development, income distribution, and carbon emissions lead to a reduction in renewable energy consumption. Therefore, to achieve its ambitious goal of generating 85% of its energy from renewable sources by 2030, the government must carefully monitor and continually analyze these interconnected macroeconomic factors. This will enable effective tailoring of policies and interventions, paving the way for a successful transition to clean and renewable energy.
Keywords: energy transition; macroeoconomic determinant; Madagascar; renewable energy; renewable energy consumption